2017
DOI: 10.1002/sim.7275
|View full text |Cite
|
Sign up to set email alerts
|

Estimating efficacy in trials with selective crossover

Abstract: When one arm in a trial has a worse early endpoint such as recurrence, a data‐monitoring committee might recommend that all participants are offered the apparently superior treatment. The resultant crossover makes it difficult to measure differences between arms thereafter, including for longer‐term endpoints such as mortality and disease‐specific mortality. In this paper, we consider estimators of the efficacy of treatment on those who would not cross over if randomised to the apparently inferior arm. Binomia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…When 1 arm has a worse early endpoint, the resultant crossover confounds differences in late endpoints, such as survival, between the 2 arms. 8 The main oncological outcome of the study reported by Sandstro ¨m et al is presented in Figure 2, which displays the overall survival based on an intention-to-treat design. Although these findings are impressive, one could argue that the final conclusions should also be drawn from Figure 3, which represents a more direct comparison of the 44 patients who completed ALPPS with the 27 patients who completed TSH, excluding those with rescue ALPPS.…”
Section: Rescue After Failure Of the First Stage Of Tshmentioning
confidence: 99%
See 1 more Smart Citation
“…When 1 arm has a worse early endpoint, the resultant crossover confounds differences in late endpoints, such as survival, between the 2 arms. 8 The main oncological outcome of the study reported by Sandstro ¨m et al is presented in Figure 2, which displays the overall survival based on an intention-to-treat design. Although these findings are impressive, one could argue that the final conclusions should also be drawn from Figure 3, which represents a more direct comparison of the 44 patients who completed ALPPS with the 27 patients who completed TSH, excluding those with rescue ALPPS.…”
Section: Rescue After Failure Of the First Stage Of Tshmentioning
confidence: 99%
“…In this situation, sequential HVE could be performed instead of the first stage of ALPPS; HVE could be performed under local anesthesia and light sedation, on an outpatient basis, and, most importantly, with no risk of severe morbidity or mortality. When 1 arm has a worse early endpoint, the resultant crossover confounds differences in late endpoints, such as survival, between the 2 arms 8 …”
Section: Clinical Commentsmentioning
confidence: 99%
“…Other types of switching occur – switching is sometimes triggered by an interim analysis [28] or patients may switch on to treatments other than those under investigation in the RCT [1, 5]. The type of switching may influence whether adjustment is appropriate, and what the target of estimation should be [29] but these issues are not the focus of this study. We use the simulation study previously reported by Latimer et al [18] but extend it to include the TSE method in combination with IPCW in addition to the previously investigated TSE with and without re-censoring methods.…”
Section: Introductionmentioning
confidence: 99%